Sorbents for high-temperature removal of alkali metals and HCl from municipal solid waste derived syngas - Zhao, Ya (2022)
Impurities such as alkali metals (NaCl and KCl) and hydrogen chloride can limit downstream syngas utilization. In this study, a highly-active sorbent based on alumina containing active components for alkali metals and HCl sorption was synthesized for simultaneous removal of alkali metals and HCl from syngas at high temperatures of 750-850 °C in a reactor and compared with other sorbents (kaolin and γ-Al2O3). Results revealed that the removal efficiency of the developed sorbent for NaCl, KCl and HCl was the highest compared to kaolin and γ-Al2O3. At optimized conditions, the simultaneous alkali metal and HCl removal efficiencies were >80% and >70%, respectively (≤850 °C). Experimental data and thermodynamic calculations suggest that the removal of alkali metals was predominantly governed by physical sorption, while the removal of HCl was governed by chemical sorption. The physicochemical adsorption interactions between the sorbent and NaCl, KCl and HCl contributed to the simultaneous removal of alkali metals and HCl.